LEGAL THEORIES OF UNJUST ENRICHMENT IN COMMERCIAL DISPUTES - Gao XinXin, (Ustozlar uchun, 2025)
Abstract:This study offers a thorough examination of unjust enrichment as a legal concept, with a specific focus on its relevance to commercial litigation within Uzbekistan. It investigates the essential attributes and underlying jurisprudential principles that define unjust enrichment, setting it apart from obligations arising in contract and tort. Utilizing comparative methodologies, real-world examples, and judicial precedents, the paper identifies key uncertainties, intersections, and procedural difficulties present in current legal practice. The discussion underscores the need for a more coherent and structured approach to unjust enrichment in order to foster equitable outcomes and reinforce legal predictability in commercial dealings. Incorporating international legal models and scholarly perspectives, the paper proposes actionable reforms, institutional enhancements, and compliance measures designed to support legal development and enhance the commercial regulatory framework in Uzbekistan.